SPEECH ACT AND POLITENESS TRATEGY USED BY PRE-SERVICE TEACHER IN ONLINE LEARNING IN SMA LAB UNDISKSHA - I Gede Rizky Aditiya; I Nyoman Adi Jaya; Dewa Putu Ramendra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Language is an essential tool that we use in our daily life. In general, language is used as a toolto convey information. In using language, speakers must pay attention to the language used.Language users should do this to avoid or minimize errors in conveying information to listeners. Thisstudy aims to determine what types of speech acts and politeness strategies are used by pre-serviceteachers when teaching online classes. This research is expected to provide an overview of how speechacts and politeness strategies can affect educational activities. This research is a qualitative descriptivestudy. This research was conducted using two steps. The researcher's first step is to observe how preserviceteachers use speech act and politeness strategies in online classes. Then the researcher willconduct interviews with research subjects or pre-service teachers to verify the data that has beenobserved. In conducting this research, the researcher used two theories as to the research foundation.The first theory is Searle's theory of speech act types and Brown and Levinson's theory of politenessstrategies. The study found that if pre-service teachers use five types of speech acts, they arerepresentative, directive, commissive, expressive, and directive. This study also found that pre-serviceteachers used more directive speech acts in teaching online classes than other types of speech acts. Inaddition to the use of speech acts, this study also found that pre-service teachers also use fourpoliteness strategies in teaching online classes. The four types of politeness strategies are bald-onrecord,positive politeness, negative politeness, and off-record.